The role of digitalization in the growth of sustainable development - Sysolyatin Alexey; Kushova Irina; Rudenko Lyudmila; Mottaeva Angela; Zhilkina Tatyana (BIO Web of Conferences)
The formation of sustainable environment under the influence of scientific and technological progress contributes to active digital modernization in various directions, from the formation of an information society to the launch of an e-government system. Digitalization of all areas of life is becoming today a necessary requirement for the sustainable development of countries and regions that want to ensure stable growth and competitiveness in a dynamic and changing world. The key of these areas was the introduction of high-tech developments in entrepreneurship, since the implementation of this area has the most pronounced systemic impact on the competitiveness of economic systems. Therefore, analysis of the level of digitalization of regional economic systems on the territory of the Russian Federation is necessary to achieve sustainable development goals (ESG). The purpose of this article is to assess and analyze the process of digitalization of the economy based on open data.. The materials of the article supplement the concept of digitalization of the Russian economy with empirical data, reveal growth points in the implementation of the digital transformation strategy of the Novosibirsk region, which allows for a more balanced approach to the formation of its new high-tech digital markets and sectors, as well as the management of sustainable development.